2012
DOI: 10.1001/archopthalmol.2011.1921
|View full text |Cite
|
Sign up to set email alerts
|

The Cost-effectiveness of Welcome to Medicare Visual Acuity Screening and a Possible Alternative Welcome to Medicare Eye Evaluation Among Persons Without Diagnosed Diabetes Mellitus

Abstract: Objective To estimate the cost-effectiveness of visual acuity screening performed in primary care settings and of dilated eye evaluations performed by an eye care professional among new Medicare enrollees with no diagnosed eye disorders. Medicare currently reimburses visual acuity screening for new enrollees during their initial preventive primary care health check, but dilated eye evaluations may be a more cost-effective policy. Design Monte Carlo cost-effectiveness simulation model with a total of 50 000 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…The US Preventive Services Task Force recently stated there was insufficient evidence to assess the harms and benefits of screening for impaired visual acuity in older adults; however in their review of the current evidence they did find consistent evidence that screening for visual acuity can identify individuals with refractive error (Siu et al, 2016). While the effectiveness of screening for vision impairment in primary care is still to be determined, dilated eye evaluations have been found to be more cost effective than standard vision tests during an initial preventive physical examination upon enrollment in Medicare (Rein et al, 2012). Future research should examine the both the effectiveness and cost-effectiveness of screening for visual acuity and providing low cost corrective lenses, as well as consider which services will be reimbursed by insurance.…”
Section: Discussionmentioning
confidence: 99%
“…The US Preventive Services Task Force recently stated there was insufficient evidence to assess the harms and benefits of screening for impaired visual acuity in older adults; however in their review of the current evidence they did find consistent evidence that screening for visual acuity can identify individuals with refractive error (Siu et al, 2016). While the effectiveness of screening for vision impairment in primary care is still to be determined, dilated eye evaluations have been found to be more cost effective than standard vision tests during an initial preventive physical examination upon enrollment in Medicare (Rein et al, 2012). Future research should examine the both the effectiveness and cost-effectiveness of screening for visual acuity and providing low cost corrective lenses, as well as consider which services will be reimbursed by insurance.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study estimated that the global cost of establishing and operating educational and refractive care facilities to deal with VI resulting from uncorrected refractive error was far below the global loss in productivity associated with that VI [ 14 ]. Another study reported that a dilated eye evaluation was cost-effective when compared to no screening [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Even though our original recommendation of positioning the sutures 1 mm from the limbus to simulate an iris diaphragm does place the sutures in the same plane, 1 their modification helps ensure their alignment. Silicone oil retention sutures can be placed in different patterns depending on the exact pathology without sacrificing their ability to prevent silicone oil endothelial touch.…”
Section: In Replymentioning
confidence: 99%